Seroepidemiology of Chagas disease in at-risk individuals in Caraíbas, a city with high endemicity in Bahia State, Brazil - Pavan, Tycha Bianca Sabaini; Dias, Deorlan Pereira; Cangussú, Márcia Moraes; Dutra, Vilquenia Porto Pacheco; Sampaio, Daniel Dias; Santos, Fred Luciano Neves (Frontiers in Public Health, 2023)
Introduction In Brazil, an estimated 1.1 million people are infected with Trypanosoma cruzi, the causative agent of Chagas disease (CD). Despite the high number of cases, the estimated prevalence of infection per 100 inhabitants is low (0.03). However, the actual number of chronically infected individuals is still unknown. Therefore, we sought to determine the prevalence of chronic CD in at-risk individuals in Caraíbas (Bahia, Brazil) through active case finding. Methods A total of 572 individuals living in rural or urban areas of Caraíbas were eligible for the study. A serum sample was collected from 226 individuals, and the diagnosis performed according to international guidelines. Results The overall prevalence of anti-T. cruzi IgG was 4.42%. The median age of anti-T. cruzi IgG-positive individuals was 54.5 years, and the female-to-male ratio was 1.5:1. The prevalence of anti-T. cruzi IgG was similar in rural (4.29%) and urban areas (4.65%). Discussion Compared with national estimates, we concluded that Caraíbas had a high prevalence for chronic CD and a high risk for persistent transmission. Through our study, it was possible to monitor individuals who were unaware of their clinical condition, thus improving their quality of life.